Determinants of pass-through of international oil prices to domestic consumer fuel prices: evidence from Uganda - Isaac Peter OTAI; Barbara Deborah Erima BIRUNGI (The Body of Expert and Licensed Accountants of Romania, 2026)
Debtor management is a critical determinant of the financial health of small and medium-sized enterprises (SMEs). This study examined the effect of debtor management on the financial performance of hardware SMEs in Mukono, Uganda. Using Yamane’s (1967) formula at a 95% confidence level, a representative sample of 55 SMEs was determined. A stratified random sampling technique was employed to ensure coverage across municipality divisions, with a proportionate selection of respondents. Using a descriptive and correlational design, data was collected from owners, managers, and accounts staff through structured questionnaires and analysed using descriptive and regression techniques. Findings revealed that debtors’ management practices (debt collection practices and debtors turnover) positively and significantly influence financial performance (liquidity and profitability). The study concludes that effective debtor management enhances financial performance and sustainability in the hardware sector. It recommends that SMEs strengthen credit policies, adopt robust collection mechanisms, and train staff in receivables management to improve performance.
Keywords: Oil; price; fuel; Uganda; domestic